Etika berkomunikasi melalui telepon - Jauharoh, Sonia Zumna (Maliki Interdisciplinary Journal, 2025)
Communication via telephone is one of the important skills in the world of work, especially for a secretary who is tasked with assisting the leadership in running the company's operations. This research discusses various aspects of telephone communication, including the definition, types of telephones, their benefits in the world of work, and the ethics that must be applied when communicating over the phone. Telephone communication etiquette includes the use of polite language, the delivery of clear information, and politeness in receiving and making calls. In addition, this research also discusses the personality and appearance of a secretary who plays a role in reflecting the company's professional image. In conclusion, the implementation of good telephone communication ethics can improve the effectiveness of business communication as well as strengthen the positive image of the organization.